Physicochemical properties, antibacterial activity, and antioxidant capacity of mixed Sidr honey from Saudi Arabia - El-Meihy, Rasha M.; Morsy, Mohamed K.; Kasem, Sobhy I.; Aljuweer, Saud A. M.; Abdelaziz, Manal; Saddeek, Salma; Nowar, Elhosseny E. (Frontiers in Sustainable Food Systems, 2025)
IntroductionSidr honey has been used for centuries for its taste, odor, nutritive value, and therapeutic characteristics, including antibacterial and antioxidant activity. Sidr honey is high cost, and limited supply leads to frequent tampering. Honey's quality is established by its botanical origin and chemical composition, which, depending on whether it is categorized as organic, monofloral, or multifloral, are also utilized to increase sales. This study evaluated the quality parameters and antioxidant capacity of mixed Sidr honey (Sidr Al-tmayoz).MethodologyPhysicochemical, antibacterial properties, and antioxidant capacity of mixed Sidr honey (Sidr Al-tamayoz) from Saudi Arabia were performed. The Sidr Al-tamayoz was designed using three types of Sidr honey, i.e., Peshawar Sidr, Al-Barri Sidr, and Balady Sidr (1:1:1; w/w). physicochemical including pH level, total insoluble solids, hydroxymethylfurfural, hydroxymethylfurfural, sugars, diastase enzyme activity were carried out. Bioactive compounds that is, flavonoids and phenolics, also antioxidant activity (DPPH) were done. Additionally, antibacterial capacity was conducted using agar well diffusion assay.Results and discussionThe physicochemical properties of Sidr Al-tamayoz honey were moisture (16.7%), pH (5.07), acidity (20 meq/kg), electrical conductivity (0.85 mS/cm), hydroxymethylfurfural (5.1 mg/kg), and total sugars (83 g/100 g) in accordance with Codex Alimentarius. Sidr Al-tamayoz honey exhibited high phenolic (45.76 mg GA/g), flavonoid (40.66 mg R/g), and antioxidant activity (62.68%). Moreover, Sidr Al-tamayoz displayed the greatest antibacterial activity (inhibitory zones and dehydrogenase activity) out of all the pathogenic bacteria: Staphylococcus aureus, Salmonella Typhimurium, Pseudomonas aeruginosa, and Escherichia coli O157:H7.ConclusionThe findings demonstrated that Sidr Al-tamayoz honey is a promising natural product rich in bioactive compounds and antioxidants, as well as enhancing quality parameters.